Phosphorus Sorption in Some Great Soil Groups of Iraqi Kurdistan Region - Rasul, Ghafoor A. Mam; Saeed, Kamil Sabier (Sulaimani Journal for Pure and Applied Sciences, 2014)
Phosphorus (P) sorption in soils is a key process governing its availability for crops. There is scanty information on the P sorption characteristics of calcareous soils of Kurdistan region of Iraq. P sorption characteristics were determined in seven soil samples belonging to four agricultural soil great groups located in Sulaimani province. (Xerorthents, Haploxererts, Haploxerolls and Calcixerolls). Total equivalent CaCO3 contents ranged from (33.80 to 350.65 g kg-1). Active CaCO3 contents ranged from (20.00 to 150.00 g kg-1). The amount of available P contents ranged from (4.49 to 6.92 mg P kg-1soil). Langmuir and Freundlich models were applied on seven different textured calcareous soils, in order to characterize the P adsorption isotherm for these soils. Langmuir and Freundlich parameters (KL, b, Kf and 1/n) values were (130.00 to 800.00 L mg-1, 28.57 to 76.92 mg kg-1, 42.27 to 121.06 mg kg-1and 0.656 to 0.974 ) respectively. High values of (KL) for all investigated soil samples indicate a strong attraction between sorbed P and sorbent surface.
Keywords: Phosphorus; adsorption; precipitation; Langmuir and Freundlich isotherms,calcareous soils